2006
DOI: 10.1128/jcm.44.4.1342-1346.2006
|View full text |Cite
|
Sign up to set email alerts
|

Time to Blood Culture Positivity as a Predictor of Clinical Outcome of Staphylococcus aureus Bloodstream Infection

Abstract: Few studies have assessed the time to blood culture positivity as a predictor of clinical outcome in bloodstream infections (BSIs). The purpose of this study was to evaluate the time to positivity (TTP) of blood cultures in patients with Staphylococcus aureus BSIs and to assess its impact on clinical outcome. We performed a historical cohort study with 91 adult patients with S. aureus BSIs. TTP was defined as the time between the start of incubation and the time that the automated alert signal indicating growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 31 publications
7
99
6
Order By: Relevance
“…Further, studies showed that a TTP ≤ 14 h was correlated to attributable mortality in bacteremia varying from 11.9% to 18% [3,11,12]. In our study, attributable mortality (27.5%) was higher than those reported in the literature but there was no significant association between TTP and attributable mortality.…”
Section: Time To Positivity: Univariate Analysis and Predictive Valuecontrasting
confidence: 56%
See 4 more Smart Citations
“…Further, studies showed that a TTP ≤ 14 h was correlated to attributable mortality in bacteremia varying from 11.9% to 18% [3,11,12]. In our study, attributable mortality (27.5%) was higher than those reported in the literature but there was no significant association between TTP and attributable mortality.…”
Section: Time To Positivity: Univariate Analysis and Predictive Valuecontrasting
confidence: 56%
“…First, our elderly population presented an important rate of comorbidities (Charlson score ≥ 5 in 74% patients) that could have influenced mortality in SAB. However, we did not find a relation between attributable mortality and comorbidities as described in the literature [11,13,16]. The second hypothesis is the higher median age (72 years) in our cohort and the even higher age (82 years) among the deceased patients.…”
Section: Time To Positivity: Univariate Analysis and Predictive Valuecontrasting
confidence: 36%
See 3 more Smart Citations